Membranoproliferative Glomerulonephritis Type 1 Secondary to an Infected Ventriculoperitoneal Shunt: a Case Report - Paliouras Christos (BANTAO Journal, 2014)
Ventricular shunting is the usual method for treatment of congenital or acquired hydrocephalus. Immune-mediated glomerulonephritis (shunt nephritis) is a rare but life-threatening complication of this neurosurgical technique. Intraglomerular deposition of circulating immune complexes and the subsequent activation of the classical pathway of serum complement’s cascade result in glomerular inflammation. Membranoproliferative gomerulonephritis is the most common histologic pattern observed in renal biopsy. The diagnosis needs high suspicion and is based on clinical and laboratory findings. Deterioration of renal function in association with signs of infection and low levels of serum complement’s proteins C3 and C4 make the diagnosis possible. The prognosis is variable and depends on the time of diagnosis after the onset of glomerular injury. The optimal treatment includes timely removal of the infected shunt in combination with aggressive antibiotic therapy. In this paper we present the case of a membranoproliferative glomerulonephritis type 1 in a patient with a ventriculoperitoneal shunt. Although this type of shunting is considered safer than the ventriculoatrial one, the risk of complications such as an immune-mediated glomerulonephritis still exists.